2009
DOI: 10.1007/s10943-009-9255-9
|View full text |Cite
|
Sign up to set email alerts
|

The Lack of Teaching/Study of Religiosity/Spirituality in Psychology Degree Courses in Brazil: The Need for Reflection

Abstract: This study investigated the existence/non-existence of subjects on the theme of religion/spirituality, in psychology degree courses in Brazil. Data were collected from university websites and through e-mail. The data include 301 (84.6%) of all existing courses; the subject of religiosity/spirituality is incorporated into 13% of public institutions and in 16% of private institutions; 84% of the courses do not have this subject incorporated into their curricula. Actually, few programs provide formal training in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
2
3
0
6
Order By: Relevance
“…These results are in line with a recent Brazilian study which found that 84% psychology courses do not address spirituality in their curriculum, which underscores the challenges faced by academic institutions in including such courses in Brazil [16]. …”
Section: Discussionsupporting
confidence: 90%
“…These results are in line with a recent Brazilian study which found that 84% psychology courses do not address spirituality in their curriculum, which underscores the challenges faced by academic institutions in including such courses in Brazil [16]. …”
Section: Discussionsupporting
confidence: 90%
“…No âmbito da formação superior em psicologia, todavia, a abordagem do tema parece assumir percursos diferentes. Menos de um quarto dos cursos de psicologia do país oferecem disciplinas voltadas especificamente para questões relacionadas à religião em seus currículos (Costa, Nogueira & Freire, 2010;Piasson, 2017), mesmo diante do interesse latente ou expresso dos alunos, constituindo-se um tema distante das salas de aulas e contextos de supervisão (Ancona-Lopez, 2005;Paiva, 2017a).…”
unclassified
“…This might illustrate the fact that 84% of the psychology courses do not address spirituality in their curricula (Costa, Nogueira, & Freire, 2010).…”
Section: The Psychology Of Religion In the Postgraduate Programsmentioning
confidence: 99%